Obsessive-Compulsive and Post Traumatic Avoidance Symptoms Influence the Response to Antihypertensive Therapy: Relevance in Uncontrolled Hypertension - Lorenzo Calo; Andrea Semplicini; Francesca Vettore; Luisa Macchini; Matteo Leoni; Emanuela Parotto; Giulia Inverso; Marco Nuti; Paolo Santonastaso; Angela Favaro; Anna Realdi (MDPI AG, 2009)
Aim: To investigate the association of uncontrolled hypertension with psychological factors associated with high cardiovascular morbidity and mortality (type D personality, depression, posttraumatic stress-related symptoms). Methods: 205 consecutive outpatient hypertensives completed three questionnaires evaluating Type D personality (DS 16), post traumatic symptoms (revised Impact of Events Scale), symptoms of anxiety, hostility, depression and obsessive-compulsive traits (subscales of the Symptom Checklist). Uncontrolled hypertension was diagnosed when clinic sitting blood pressure was above 140/90 mmHg (130/80 in the presence of diabetes or nephropathy), despite reported adherence to treatment with at least three antihypertensive medications, including a diuretic. Results: Uncontrolled hypertension (39%), was predicted by lower scores at Symptom Checklist obsessive-compulsive subscale and higher number of post traumatic avoidance symptoms, older age, diabetes, higher systolic pressure at first visit and longstanding hypertension. Type D personality correlated with depression, hostility, anxiety, compulsiveness, history of malignancy, and older age, but not with uncontrolled hypertension. Conclusions: Uncontrolled hypertension is associated with low obsessionality and avoidance symptoms, which reduce compliance to treatment. On the contrary, type D personality is not correlated with uncontrolled hypertension, as it includes compulsiveness, which improves compliance. A multidisciplinary approach to the hypertensive patient is mandatory to establish if the psychological profile affects compliance.